Policy unplugged : dis/connections between technology policy and practices in Canadian schools - Jenson, Jennifer, 1950-; Brushwood Rose, Chloë T. (Chloë Tamara), 1972-; Lewis, Brian, 1948- (McGill-Queen's University Press, 2007)
The authors conducted a two-year study on the implementation of computer technologies, including in-depth interviews and classroom observation at thirty-two elementary and secondary schools across Canada. Based on this research, Policy Unplugged explores the intersections and disconnections between provincial technology policy, school board policy, and school-based practices. The authors consider the ways in which technology policy has become "unplugged" from daily experience, showing that teachers, students, and administrators are part of complex pedagogical and social systems that have been badly served by the enforced and hasty introduction of technology. They also show how small, often unquestioned practices and power relations in schools can create seemingly insurmountable impediments to technological implementation.